Sales Compensation and Recommendations as the Fund of the Month - Yoonhae Oh (KDI Journal of Economic Policy, 2019)
This study analyzes whether mutual fund distributors are more likely to recommend products with higher sales compensation to maximize their profit. The lists of the 'fund of the month' on their webpages are utilized from April of 2015 to August of 2015. A simple comparative analysis shows that the average sales fees and the average front-end load are significantly higher in the recommended funds among the A share class of domestic equity funds. The results of a regression analysis confirm that funds with high sales compensation levels are more likely to be recommended. This holds true for both domestic equity funds and hybrid bond funds even after controlling for fund age, fund size, and past returns.
Keywords: G20; G24; G28; 330; Mutual Fund; Sales Compensation; Conflict of Interest